Whistleblower a traitor? case study - Mohd Ali @ Ramli, Azlin Namili; A. Rahman, Aspalella; Yaacob, Nurli (Global Academic Excellence, 2018)
Speak out of misconduct, it is a right thing to do. Whistleblowers can put justice right at its place. If not because of the information provided, the misconduct will continue to occur and this may be harmful to more people, and detrimantal to a country if the wrongdoing is not stopped. However, a whistleblower need to face certain risks regarding their life, freedom, family, jobs, and even confronting some of the people who do not agree with the whistleblowing. This will be apparent when the information disclosed is a confidential secret of the government. The case study of two informants, Edward Snowden and Helve Falciani, found that they had to flee to seek asylum from other countries in order to avoid being prosecuted and punished in a country whose secret information they disclosed although such confidential information is inconsistent with democracy and the laws of the country or with international law. Using a legal research method in the form of case studies where some comparisons were made between the whistleblower cases, it was found that there were similarities and differences between the effects faced by the whistleblowers. Among the consequences is that a group of people regard them as a hero for their bravery in reporting the offenses committed by the state. Some consider them a traitor for leaking the state secrets and neglect the interests of the country.